1997
DOI: 10.1002/art.1780400106
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment of systemic lupus erythematosus with cyclosporin A

Abstract: Objective. To evaluate the efficacy of long-term treatment with cyclosporin A (CSA) in systemic lupus erythematosus (SLE).Methods. Thirty patients with SLE whose condition was either poorly responsive or unresponsive to treatment with steroids and/or cytotoxic drugs were enrolled in a prospective, nonrandomized study of CSA. Patients with hypertension or hypercreatinemia were excluded. Disease activity was evaluated according to the systemic lupus activity measure. Assessments were made prior to study entry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 19 publications
1
43
1
1
Order By: Relevance
“…Treatment of SLE with cyclosporine, which has the same mechanism of action as tacrolimus (inhibition of calcineurin activity), has also been reported. Caccavo et al [20] found that combined cyclosporine and corticosteroid therapy was effective for skin symptoms, arthritis, and serositis in 30 SLE patients, but a number of adverse drug reactions occurred. There have been other reports about that effectiveness of cyclosporine for mild symptoms of SLE [21][22][23][24][25], but the incidence of adverse drug reactions seems to be high (40-60%).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of SLE with cyclosporine, which has the same mechanism of action as tacrolimus (inhibition of calcineurin activity), has also been reported. Caccavo et al [20] found that combined cyclosporine and corticosteroid therapy was effective for skin symptoms, arthritis, and serositis in 30 SLE patients, but a number of adverse drug reactions occurred. There have been other reports about that effectiveness of cyclosporine for mild symptoms of SLE [21][22][23][24][25], but the incidence of adverse drug reactions seems to be high (40-60%).…”
Section: Discussionmentioning
confidence: 99%
“…2 Thus, in a young woman who wants to get pregnant, we approach cyclophosphamide therapy with some hesitancy. Other relevant drugs, such as mizoribine, 3 CyA, 4 and mycophenolate mofetil, 5 have been reported to be effective for lupus nephritis, with mizoribine often being used as it is believed to be relatively safe.…”
Section: Discussionmentioning
confidence: 99%
“…Caccavo et al (1997) reported on the efficacy of CsA in 30 patients with refractory SLE, including 11 IVCYresistant patients. They reported a siginificant decrease of the mean disease activity score following the initiation of CsA administration in these cases, which allowed a significant reduction of the PSL dose.…”
Section: Discussionmentioning
confidence: 99%